Using The Quality Cycle in Managing Educational Information in School Under Lopburi Primary Educational Service Office Area 1 - Sangsit, Sittichai; Chulasukhont, Phuwadon; Chucheep, Sunchai (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
The objectives of this study were: 1. to investigate the use of the quality cycle in managing educational information in schools, and 2. to compare the use of the quality cycle in managing educational information across schools based on gender, age, position, work experience, academic qualifications, and school size. The research sample included 126 school administrators and 190 teachers, selected through stratified random sampling and simple random sampling by lottery. The research instrument was a 42-item questionnaire. Data were analyzed using frequency distribution, percentage, mean, standard deviation, t-test, and one-way analysis of variance (ANOVA). Where significant differences were found, pairwise comparisons were made using the Scheffé test. The findings of the study were: 1. The use of the quality cycle in managing educational information in schools under the Lopburi Primary Education Service Area Office 1 was generally at a high level, and 2. When comparing the use of the quality cycle in managing educational information, significant differences were found in relation to work experience and academic qualifications at the 0.05 level. However, when categorized by gender, age, position, and school size, no significant differences were observed.